Extracorporeal CO2 removal and renal replacement therapy in acute severe respiratory failure in COVID‐19 pneumonia: Case report. Issue 3 (10th May 2021) - Gacitúa, Ignacio; Frías, Alondra; Sanhueza, María E.; Bustamante, Sergio; Cornejo, Rodrigo; Salas, Andrea; Guajardo, Ximena; Torres, Katherine; Figueroa Canales, Enzo; Tobar, Eduardo; Navarro, Rocío; Romero, Carlos
Abstract: The COVID‐19 pandemic significates an enormous number of patients with pneumonia that get complicated with severe acute respiratory distress syndrome (ARDS), some of them with refractory hypercapnia and hypoxemia that need mechanical ventilation (MV). Those patients who are not candidate to extracorporeal membrane oxygenation (ECMO), the extracorporeal removal of CO2 (ECCO2 R) can allow ultra protective MV to limit the transpulmonary pressures and avoid ventilatory induced lung injury (VILI). We report a first case of prolonged ECCO2 R support in 38 year male with severe COVID‐19 pneumonia refractory to conventional support. He was admitted tachypneic and oxygen saturation 71% without supplementary oxygen. The patient's clinical condition worsens with severe respiratory failure, increasing the oxygen requirement and initiating MV in the prone position. After 21 days of protective MV, PaCO2 rise to 96.8 mmHg, making it necessary to connect to an ECCO2 R system coupled continuous veno‐venous hemodialysis (CVVHD). However, due to the lack of availability of equipment in the context of the pandemic, a pediatric gas exchange membrane adapted to CVVHD allowed to maintain the removal of CO2 until completing 27 days, being finally disconnected from the system without complications and with a satisfactory evolution.